Kefiran : a multifunctional biopolymer – extraction and particle structure fabrication - Tan, Jou Ling (2019)
Kefiran is a food-based polysaccharide produced by the microorganisms present in Kefir grains. It is a recognized Generally Regarded as Safe (GRAS) product that possesses multiple health-promoting properties such as anti-inflammatory, anti-tumour, and antibacterial. The aim of this study was to investigate the feasibility of using the Kefiran polysaccharides, extracted from Kefir grains, to fabricate the particle structures. In order to achieve this, milk Kefir was cultured, and the polysaccharide was extracted from the fermented Kefir grains. From the extracted polysaccharide, Kefiran was characterised using Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and Thermogravimetric Analysis (TGA). Both FTIR and thermal analysis showed that Kefiran contains significant (20%) moisture. Thermal analysis showed a high degradation temperature of Kefiran at 237 ºC; hence, Kefiran can potentially be used in food and medical industry with processing temperature up to 150 ºC. As the Kefiran were intended for oral delivery, their behaviour in different gastrointestinal tract (GIT) fluids was studied using simulated GIT fluids. Given the presence of enzyme amylase, the salivary, intestinal, and colonic conditions were found to be optimum for the degradation of Kefiran. The feasibility of making particles structures was studied through different methods such as emulsion cross-linking, direct injection, and flash freezing with liquid nitrogen. Kefiran particles of 1.5-2.0 mm in diameter were obtained from injection precipitation and liquid nitrogen method.